2006
DOI: 10.1177/1062860605280314
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers to Pneumococcal Vaccination in Patients With Pneumonia

Abstract: Inpatient pneumococcal vaccination remains underutilized, and little data exist to guide hospital personnel in improving their performance. The authors report their experience with a stepwise program to improve vaccination assessment rates for hospitalized patients with community-acquired pneumonia. They assessed barriers to vaccination and applied a stepwise educational and intranet-based decision support implementation program for hospitalized patients with community-acquired pneumonia. Preintervention vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Limitations of this study should be mentioned. Some variables that are known to be related to inadequate vaccination could not be analyzed because they were not collected for the major study [ 9 , 35 , 41 43 ]. Due to the short time elapsed between the introduction of PCV10 and data collection, it was not possible to compare coverage and compliance of schedules of 2 and 3 primary doses without the booster dose to schedules of 2 and 3 primary doses with the booster dose.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this study should be mentioned. Some variables that are known to be related to inadequate vaccination could not be analyzed because they were not collected for the major study [ 9 , 35 , 41 43 ]. Due to the short time elapsed between the introduction of PCV10 and data collection, it was not possible to compare coverage and compliance of schedules of 2 and 3 primary doses without the booster dose to schedules of 2 and 3 primary doses with the booster dose.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the negative results observed in the study by Harris et al [27,28] may have resulted from an approach that only targeted one aspect of care—patient education. Other studies, based in the acute care setting, have shown that interventions that consist of education alone do not result in significant increases in influenza and pneumococcal vaccination rates [35]. The positive results observed in the before-after study by Bhatt et al [32] highlights the importance of using a multimodal approach to improve the rate of influenza and pneumococcal vaccination in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…This poor rate of vaccination may probably be related to the fact that there are presently no locally available guidelines for vaccination of adults and at-risk population in 10,14 Nigeria. However, this may not entirely be the sole reason, as poor vaccination rate has also been documented in developed countries with [19][20][21][22][23][24] pneumococcal vaccination guidelines. The practice of adult vaccination against vaccine preventable diseases (VPDs) in Nigeria has been very poor even though the knowledge and awareness of vaccine preventable diseases among adult physicians have been found to be above However, lack of proper awareness of the disease by health care providers, failure to assume responsibility for vaccination by the managing physicians, competing priorities, incomplete or inaccessible records of previous vaccines, and various health care system challenges were also reported by Rehm et al as and recommendation from their physician, especially cardiologists, were significantly more 22 likely to be vaccinated.…”
Section: Table 3: Socio-demographic and Clinical Profile Of The Vacci...mentioning
confidence: 99%